Interleukin-6 Receptor Gene 48892 A/C Polymorphism Is Associated with Metabolic Syndrome in Female Taiwanese Adolescents - Hsieh, Chang-Hsun (Mary Ann Liebert, Inc., 2012)
Background: This study was to evaluate the relationship between the interleukin-6 receptor (IL-6R) 48892 A/C single-nucleotide polymorphism (SNP) (rs8192284) and the metabolic syndrome (MetS) and its components among young adolescents in Taiwan. Methods: We enrolled 925 adolescents (451 boys and 474 girls). Modified National Cholesterol Education Program Adult Treatment Panel-III (NCEP ATP-III) criteria were applied to define MetS (with age- and gender-specific 90th percentile cutoff point of variables). Subjects had three or more of the following cardiometabolic abnormalities that occur in MetS: high blood pressure, high fasting glucose, high triglyceride (TG), low high-density lipoprotein cholesterol (HDL-C), and obesity. The characteristics of the MetS components associated with different alleles and genotypes of the IL-6R rs8192284 SNP were compared. Results: Frequencies of alleles and genotypes of the IL-6R 48892 polymorphism were similar in both sexes. Boys with C-alleles had borderline lower TG levels than A-allele carriers (66.0±30.1 vs. 70.3±34.6 mg/dL, p=0.07). However, girls with C-alleles had higher waist circumference (WC) (68.0±7.9 vs. 67.0±7.7 cm) and lower HDL-C levels (50.7±11.1 vs. 52.2±11.7 g/dL) than A-allele carriers (p=0.05). The prevalence of MetS and its components, high WC and low HDL-C level, were higher in female C-allele carriers (all p<0.05) but not in boys. The odds ratios for high WC, low HDL-C levels, and MetS for female C-allele carriers were 1.54 (95% confidence interval [CI]: 1.01–2.34), 1.49 (95% CI: 1.01–2.18), and 2.19–2.39 (95% CI: 1.15–4.51), respectively, when compared with A-allele carriers. Conclusions: The IL-6R 48892 A/C polymorphism is associated with high TG and WC, and low HDL-C levels in adolescents. Additionally, there is a gender difference in the incidence of MetS, indicating a possible gene–gender interaction of the IL-6R 48892 A/C polymorphism in MetS among Taiwanese adolescents.